Credible Commitment to Optimal Escape from a Liquidity Trap : The Role of the Balance Sheet of an Independent Central Bank - Jeanne, Olivier; Svensson, Lars. (Washington, D.C. : International Monetary Fund, 2004)
An independent central bank can manage its balance sheet and its capital so as to commit itself to a depreciation of its currency and an exchange rate peg. This way, the central bank can implement the optimal escape from a liquidity trap, which involves a commitment to higher future inflation. This commitment mechanism works even though, realistically, the central bank cannot commit itself to a particular future money supply. It supports the feasibility of Svensson's Foolproof Way to escape from a liquidity trap.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet